Pengetahuan dan Sikap Mencuci Tangan Yang Benar Menurut Kesehatan - Sherly Eristiana Sari; Darmiah Darmiah; Imam Santoso; Erminawati Erminawati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2018)
Abstract: Knowledge and Attitude of Proper Handwashing According to Health. Getting used to wash hands with soap (CTPS) is the same as teaching children and all family members to live healthy early has an important role in relation to disease prevention, such as diseases of worms and can serve to reduce microorganisms in the hands. The purpose of this research was to know the application of PHBS about the knowledge and attitude of proper hand washing according to health in Elementary School Regency of Hulu Sungai Selatan. The research design was descriptive, cross sectional research design. Data coection used questionnaires that were filled directly by students. The population of the study were 110 students, the sampling using Proportional Random Sampling technique was obtained by 51 students. The results showed enough knowledge categories as many as 20 students (39.22%), less as many as 31 students (60.78%). Good attitude category as many as 39 students (76.47%), quite as many as 7 students (13,72%) and attitude which still less as much as 5 student (9.80%). The conclusion of the research of students' knowledge about proper hand washing according to health, has enough category, even more that still less, while student attitude has been included good category. It is advisable to make efforts to increase the knowledge through the extension method of Clean and Healthy Behavior (PHBS), especially hand washing properly according to the health routinely by school and related institution such as local health center.